Physiological levels of chromogranin A prevent doxorubicin‐induced cardiotoxicity without impairing its anticancer activity. Issue 6 (11th April 2019) - Rocca, Carmine; Scavello, Francesco; Colombo, Barbara; Gasparri, Anna Maria; Dallatomasina, Alice; Granieri, Maria Concetta; Amelio, Daniela; Pasqua, Teresa; Cerra, Maria Carmela; Tota, Bruno; Corti, Angelo; Angelone, Tommaso
ABSTRACT: The clinical use of doxorubicin (Doxo), a widely used anticancer chemotherapeutic drug, is limited by dose‐dependent cardiotoxicity. We have investigated whether chromogranin A (CgA), a cardioregulatory protein released in the blood by the neuroendocrine system and by the heart itself, may contribute to regulation of the cardiotoxic and antitumor activities of Doxo. The effects of a physiologic dose of full‐length recombinant CgA on Doxo‐induced cardiotoxicity and antitumor activity were investigated in rats using in vivo and ex vivo models and in murine models of melanoma, fibrosarcoma, lymphoma, and lung cancer, respectively. The effect of Doxo on circulating levels of CgA was also investigated. In vivo and ex vivo mechanistic studies showed that CgA can prevent Doxo‐induced heart inflammation, oxidative stress, apoptosis, fibrosis, and ischemic injury. On the other hand, CgA did not impair the anticancer activity of Doxo in all the murine models investigated. Furthermore, we observed that Doxo can reduce the intracardiac expression and release of CgA in the blood ( i.e ., an important cardioprotective agent). These findings suggest that administration of low‐dose CgA to patients with low levels of endogenous CgA might represent a novel approach to prevent Doxo‐induced adverse events without impairing antitumor effects.—Rocca, C., Scavello, F., Colombo, B., Gasparri, A. M., Dallatomasina, A., Granieri, M. C., Amelio, D., Pasqua, T., Cerra, M. C., Tota, B., Corti, A., Angelone, T. Physiological levels of chromogranin A prevent doxorubicin‐induced cardiotoxicity without impairing its anticancer activity. FASEB J. 33, 7734–7747 (2019). www.fasebj.org